Firms, Informality, and Development: Theory and Evidence from Brazil - Ulyssea, Gabriel (American Economic Review, 2018)
This paper develops and estimates an equilibrium model where heterogeneous firms can exploit two margins of informality: (i) not register their business, the extensive margin; and (ii) hire workers “off the books,” the intensive margin. The model encompasses the main competing frameworks for understanding informality and provides a natural setting to infer their empirical relevance. The counterfactual analysis shows that once the intensive margin is accounted for, firm and labor informality need not move in the same direction as a result of policy changes. Lower informality can be, but is not necessarily associated with higher output, TFP, or welfare. (JEL D22, E26, H26, J46, O14, O17)